Research of Enhancing Rotation Fatigue Property of Small Size Engine Strengthening Silent Chain - Fei Kan; Zhang Shiqiang (Jixie chuandong)
Enhancing the performance of automobile and motorcycle engines strengthened timing silent chain rotation fatigue will contribute to improving the life of engine timing strengthened silent chain and makes the engine timing chain with the same life of engine. By means of chain plate stamping,crushing hole,heat treatment process,strengthening pretension technology and other means to enhance the performance of the timing chain rotation fatigue significantly. The analysis and experimental verification about the measures to enhance the property of timing chain rotary fatigue are carried out,the overall level of quality of the silent chain is improved.